Pendidikan Islam Menghadapi Tradisi, Transisi, dan Modernisasi - Ichsan, Ahmad Shofiyuddin; Sembiring, Ichlasul Diaz; Luthfiah , Naurah (Fitrah: Journal of Islamic Education, 2020)
Islamic education faces many challenges in the current era of globalization. Some relate to tradition, transition and modernization, and of course Islamic education cannot avoid it. The purpose of this research is to find out how Islamic educational institutions face tradition, transition, and modernization so that their existence can still be accepted by the community and remain able to compete with non-Islamic educational institutions. The results of this study are to deal with traditions, transitions and modernization that must be carried out in Islamic education is to improve and enhance the overall education system in Islamic education institutions themselves, both in terms of the ability of teachers in the use of technology, curriculum implementation that is tailored to the needs of the community while still being emphasizing the objectives of Islamic education, carrying out various educational innovations that aim to improve student learning, so as to produce students who are smart, honest, disciplined, and remain devoted to Allah SWT.